Clinicopathological predictors of long-term benefit in breast cancer treated with neoadjuvant chemotherapy - Castaneda, Carlos A (2018)
AIM To investigate the survival impact of clinicopathological factors, including pathological complete response (pCR) and tumor-infiltrating lymphocytes (sTIL) levels according to subtypes, in breast cancer (BC) patients who received neo-adjuvant chemotherapy (NAC). METHODS We evaluated 435 BC patients who presented and received NAC at the Instituto Nacional de Enfermedades Neoplasicas from 2003 to 2014. sTIL was analyzed as the proportion of tumor stroma occupied by lymphocytes, and was prospectively evaluated on hematoxylin and eosin-stained sections of the preNAC core biopsy. pCR was considered in the absence of infiltrating cancer cells in primary tumor and axillary lymph nodes. Analysis of statistical association between clinical pathological features, sTIL, pCR and survival were carried out using SPSSvs19. RESULTS Median age was 49 years (range 24-84 years) and the most frequent clinical stage was III B (58.3%). Luminal A, Luminal B, HER2-enriched and (triple-negative) TN phenotype was found in 24.6%, 37.9%, 17.7% and 19.8%, respectively. pCR was observed in 11% and median percentage of sTIL was 40% (2%-95%) in the whole population. pCR was associated to Ct1-2 ( P = 0.045) and to high sTIL ( P = 0.029) in the whole population. There was a slight trend towards significance for sTIL ( P = 0.054) in Luminal A. sTIL was associated with grade III ( P < 0.001), no-Luminal A subtype ( P < 0.001), RE-negative ( P < 0.001), PgR- negative ( P < 0.001), HER2-positive ( P = 0.002) and pCR ( P = 0.029) in the whole population. Longer disease-free survival was associated with grade I - II ( P = 0.006), cN0 ( P < 0.001), clinical stage II ( P = 0.004), ER-positive ( P < 0.001), PgR-positive ( P < 0.001), luminal A ( P < 0.001) and pCR ( P = 0.002). Longer disease-free survival was associated with grade I - II in Luminal A ( P < 0.001), N0-1 in Luminal A ( P = 0.045) and TNBC ( P = 0.01), clinical stage II in Luminal A ( P = 0.003) and TNBC ( P = 0.038), and pCR in TNBC ( P < 0.001). Longer overall survival was associated with grade I - II ( P < 0.001), ER-positive ( P < 0.001), PgR- positive ( P < 0.001), Luminal A ( P < 0.001), cN0 ( P = 0.002) and pCR ( P = 0.002) in the whole population. Overall survival was associated with clinical stage II ( P = 0.017) in Luminal A, older age ( P = 0.042) in Luminal B, and pCR in TNBC ( P = 0.005). CONCLUSION Predictive and prognostic values of clinicopathological features, like pCR and sTIL, differ depending on the evaluated molecular subtype.